A princesa não precisa ser salva: uma reflexão sobre a percepção das mulheres no desenvolvimento de jogos digitais - Morais, Priscilla Vasconcelos de (2020)
This research aims to highlight the perception of women as characters of digital games, as consumers of digital games and especially as developers of digital games. The assumption is that the growth of female audiences as consumers of games, also increases interest in working in the field, reflects on the industry by increasing the number of women working with digital games and thus may increase the number of female characters protagonists. in games. As a general objective, this paper aims to verify the participation of women in the digital games industry in Brazil, considering their role in the development of indie and triple A games in the national market and difficulties encountered by gender issues. What justifies the accomplishment of this work is that the digital games market in Brazil is so recent that few researches are done in relation to the area, mainly researches related to the professionals of the digital games especially the women who work in this market. The motivation of this research is to identify the profile of women in the digital games market. This paper aims to answer the following question: “How is the participation of women in the development of digital games in Brazil”? For the review of related studies, studies focusing on female perception in digital games were analyzed. Due to the theoretical and empirical objectives of this study, it was decided to use the methodological procedures of the bibliographic and field research, the data collection instrument was made through a questionnaire available online. Among the references for the development of the main concepts are Huizinga (2014), Callois (1990), Schell (2011), Brown, Wang and Santana (2018). The paper concludes with the presentation of the results demonstrating that women are still a minority in the digital gaming market and most of them are in the artistic field of gaming